(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1923)
In the previous season of excavation, after determining that the ground examined had been under continuous occupation, at least during the period from the end of the first to the beginning of the fifth centuries AD, the excavators reverted to the original method of removing the ground in four more or less arbitrary levels of occupation. This method was continued during the present year, and therefore the plans do not represent accurately the actual conditions existing at any particular period. However, the method of removing the soil in four levels has a certain stratigraphical value, as it aids in approximately dating the relics recovered. Two further areas were excavated along with minor investigations elsewhere on the hill. The features identified and the associated relics are described in detail. One of the gateways penetrating the rampart at the west end of the hill was also examined.